Efektivitas Ekstrak Buah Pir Dalam Menghambat Streptococcus Pyogenes Pada Media NA : Effectiveness of Pear Fruit Extract in Inhibiting Streptococcus Pyogenes in NA Media - Aditami, Tanzilal; Jannah, Ena S A R; Maharani Putri, Zahra (BiosciED: Journal of Biological Science and Education, 2025)
This study aims to determine the effectiveness of pear fruit extract (Pyrus pyrifolia) in inhibiting the growth of Streptococcus pyogenes in vitro using the disk diffusion method on Nutrient Agar (NA) media. Infection by Streptococcus pyogenes is the main cause of acute pharyngitis and often shows resistance to certain antibiotics, so natural treatment alternatives are needed. Pear fruit extract was tested at concentrations of 25%, 50%, 75%, and 100%. The test was conducted using the disk diffusion method on Nutrient Agar (NA) media, with inhibition zone measurements taken after incubation for 48 hours at 37°C. The results showed that all concentrations of the extract were able to form inhibition zones, with the 100% concentration producing the largest inhibition zone. Analysis showed a correlation between increasing extract concentration and antibacterial effectiveness, although it was not completely linear. The content of phytochemical compounds such as flavonoids and phenols in pears is thought to play a role in disrupting bacterial cell membranes and cell metabolism. This study supports the potential of pears as a natural antibacterial agent against Streptococcus pyogenes and contributes to the development of natural-based therapies to overcome antibiotic resistance.